Melanoacanthoma, Plasma Cell Cheilitis and Langerhans Cell Hyperplasia on the Lower Lip: An Unusual Association and Immunohistochemical Analysis - Silva, Evânio V. [UNESP]; Silveira, Heitor A. [UNESP]; Nogueira, Gustavo M.; Campos, Ana C.; Da Silva, Anderson T. F.; León, Jorge E. (Wolters Kluwer, 2022)
Oral melanoacanthoma is an uncommon reactive lesion, characterized by basal and prickle cell keratinocyte proliferation surrounded by pigment-laden dendritic melanocytes. Plasma cell cheilitis (PCC) is an inflammatory disorder of unknown aetiology, microscopically presenting a dense plasma cell infiltrate. Most PCC cases affect the lower lip. Langerhans cell hyperplasia (LCHyp), a non-neoplastic counterpart of the LC proliferations, has been reported in association with chronic inflammatory skin diseases. Here, we present an unusual association of melanoacanthoma, PCC and LCHyp on the lower lip in a 59-old-year male, expanding the clinicopathological spectrum of these uncommon lesions. The dendritic melanocytes were highlighted by Fontana-Masson stain and HMB-45, whereas S100, CD1a and CD207 evidenced numerous LCs. MUM1/IRF4, EMA, and CD138 highlighted sheets of polyclonal plasma cells, with an IgG4+/IgG+ ratio of 24%. FTA-ABS test for syphilis was negative.
Keywords: Immunohistochemistry; langerhans cell hyperplasia; lower lip; melanoacanthoma; plasma cell cheilitis